Gardnerella vaginalis caracterización clínica y diagnóstico de laboratorio en mujeres en edad fértil - Sarango Alvarado, Aurora Elizabeth (2022)
ABSTRACT: The objective of this study was to analyze Gardnerella vaginalis, its clinical characterization, and laboratory diagnosis in women of childbearing age who are more likely to develop bacterial vaginosis. This infection can harm women of any age, although the cause is unknown. I fully understand that certain activities, such as having unprotected sex, and frequent douching, increase the risk of contracting it. The disease can be asymptomatic or with leucorrhoea and vulvar burning. In particular women, it causes severe obstetric and gynecological complications. He carried out a descriptive investigation for the study because it dealt with a bibliographic review. It compiled updated data according to the design. It is a documentary based on information presented in scientific articles, virtual platforms, and digital books. This work had a temporal, chronological sequence of cross-sectional and retrospective type because the beginning of the study was after the facts were studied. It was also based on writings by other authors who were analyzed and discussed. The population comprised 90 scientific documents addressing the subject to be explored, with the publication period between 2012 and 2022. The sample was made up of 67 bibliographic reviews available in the databases. Conclusions: One of the main clinical manifestations is itching and abundant abnormal vaginal discharge. The main predominant infection factor is vaginal douching, and the method considered Gold Standard is the Nugent scoring system for providing greater sensitivity and specificity